Analisis Kepuasan Konsumen terhadap Pelayanan Kopi Nako Kota Wisata Cibubur - Wahid Aldi Rinanto; Puspita Romadhona (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to analyze customer satisfaction with nako coffee services in kota wisata cibubur. This research uses a qualitative descriptive method. Data collection was carried out through observation, survey, and interviews with 20 sources, namely consumers who were Visiting Kopi Nako Kota Wisata Cibubur. The results of this study are the services provided by Kopi Nako Kota Wisata Cibubur have met the criteria for good service readiness. Kopi Nako Kota Wisata Cibubur has provided good service to consumers. The analysis was carried out using indicators of reliability (reliability), responsiveness, assurance, attention (empathy), and physical evidence (tangible) which were analyzed through interviews with consumers as many as 20 sources, and they stated that they had a relatively high level of satisfaction with the services provided by kopi nako kota wisata cibubur. Keywords: satisfaction, service, consumer